“Bien Vivir” Entre el “desarrollo” y la Des/Colonialidad del Poder - Quijano, Aníbal (2023)
In this essay, one of the last he published, Aníbal Quijano opens the debate on a fundamental issue to understand the world in which we live: the root crisis of the colonial/modern/Eurocentric pattern of power and good living as a historical option for the future . After questioning the development discourse, which sought to modify power relations in Latin America, it examines the new historical period characterized by “the root crisis of the global coloniality of power” and by the emergence of a new resistance that aims at the /coloniality of power. In the midst of the crisis of coloniality/modernity/Eurocentricity, a new horizon of historical meaning is emerging: good living as “the continuous democratic production of social existence” that implies the emergence of another possible world, that is, equality. social, reciprocity in work relationships, communal association as the mode of direct production and management of collective authority.